Immediate effects of myofascial release maneuver applied in different lower limb muscle chains on postural sway. (January 2021) - Queiroz dos Santos, Albert Nunes; Lemos, Thiago; Duarte Carvalho, Pedro Henrique; Ferreira, Arthur Sá; Silva, Julio Guilherme
Abstract: Background: There is little evidence about the myofascial release maneuver (MLM) targeting the fascial tissue and its effect on postural balance. This study investigated the immediate effects of the MLM in different lower limb muscle chains on the postural sway of healthy men. Methods: Sixty-three healthy men (27.2 ± 4.7 years) were randomly assigned to 7 groups (n = 9 each) to receive MLM applied to the lower limb muscle chains (anterior, posterior, medial, lateral, anterior/posterior, and medial/lateral) or placebo intervention. Skin pressure during the 3-min MLM was determined by the visual analog scale between 5 and 7 as previously assessed on participants. Posturography analysis of the elliptical area ( Area ) and average velocity ( Vavg ) of the center-of-pressure displacement was performed before and immediately after the MLM in single-leg support and with eyes closed. Results: A two-way repeated measures analysis of variance showed no interaction effect of factors group and time ( Area : p  = 0.210, ω 2  = 0.004; Vavg : p  = 0.358, ω 2  < 0.001). Within-factor main effect of time was observed for both Area ( p  < 0.001, ω 2  = 0.038) and Vavg ( p  < 0.001, ω 2  = 0.028), with decreased Area and Vavg after all interventions. No between-factor main effect of group was observed for Area or Vavg (MLM or placebo, p  = 0.188 or higher). Conclusion: MLM applied to the lower limb muscle chains showed no immediate specific effects on postural sway in healthy men. Pre-post effects of MLM were not different from those elicited by a superficial massage. MLM in lower limb muscle chains is not advocated for an immediate improvement of postural balance in this population.